Anticorpos IgY anti-Strongyloides venezuelensis: produção, caracterização e aplicação no imunodiagnóstico da estrongiloidiase humana - Faria, Lucas Silva de (2017)
In view of the epidemiological problem of the neglected condition of human strongyloidiasis, a rapid and effective diagnosis is extremely important. The development of new diagnostic tools is essential to avoid hyperinfections and chronic cases in the course of this geohelminthiasis. IgY technology is an alternative for antibody production with high specificity and profitability. This study aimed to produce and fracionate IgY antibodies from egg yolks of hens immunized with total antigenic extracts of Strongyloides venezuelensis infectious filariform larvae (iL3) and parthenogenetic females (pF). The IgY antibodies produced were evaluated by the recognition of parasitic proteins, life forms and serological diagnosis of human strongyloidiasis. They were also used for the selection of phage clones with expressed peptides binding of the IgY molecules by phage display, for immunodiagnostic application of the disease. Five immunizations were performed with Freund's adjuvants at 14-day interval. Eggs and serum samples were obtained to monitor the production of specific antibodies. Egg yolks were purified by water dilution method and protein precipitation by ammonium sulfate, followed by fractionation in tiophilic interaction chromatography. The fractionation and antibodies specificity were confirmed by dot-blot, electrophoresis, enzyme linked immunosorbent assay (ELISA), ELISA avidity, immunoblotting and immunofluorescence antibody test (IFAT). Applications in the immunodiagnostic of strongyloidiasis, using human serum samples, were performed by detection of immune complexes with IgY antibodies by ELISA, and by detection of circulating IgG, with peptide-fused clones selected in two different biopanning strategies, by phage-ELISA. Proteins from heavy (65kDa) and light (22-24kDa) chains of IgY molecules were visualized on 12 % SDS-PAGE. The specificity was confirmed by recognition of protein bands from the total extracts and by IFAT in histological sections of S. venezuelensis (iL3 and pF). Antibodies showed levels of avidity ranging from 68.0 % to 95.4 %. The detection of immune complexes in serum samples showed diagnostic values of sensitivity (Se) and specificity (Sp) for anti-iL3 IgY and anti-Fp IgY antibodies respectively: Se: 95.56 % and Sp: 88.89 %; Se: 95.56 % and Sp: 91.11 %. Biopanning strategies selected phage clones fusedpeptides with structures similar to Strongyloides stercoralis proteins, which caused the infection in humans. Six main phage clones were identified, being two (C12 and D4) considered with the best diagnostic values for IgG detection in human serum samples (D4 - Se: 82.2 %, Sp: 83.3 %, C12 - Se: 80.0 %, Sp: 82.2 %). IgY technology can be an important tool for the strongyloidiasis study with possibilities for application in disease therapeutics and as a serological diagnostic method.